2022
DOI: 10.1108/ijesm-02-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energy consumption, CO2emissions and trade balance nexus in OECD countries: evidence from ARDL bounds approach

Abstract: Purpose Renewable energy is at the forefront of countries’ concerns due to its global economic and environmental impacts. Previous studies have thoroughly examined the impact of renewable energy on overall national income, and this paper aims to shed light on an indicator that has received insufficient attention in research regarding its impact on economic growth, using data from 2000 to 2018. Design/methodology/approach This study examines the causal relationship between trade balance, renewable energy cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Additionally, the results indicate that the variables adjust to their long‐run equilibrium at a slow rate, suggesting that short‐run disequilibria persist, which may require policy interventions to promote a more sustainable green economy in the MENA region. Previous research on the relationship between economic growth and energy consumption supports the results of this study, see (Mohammed Idris et al., 2022).…”
Section: Resultssupporting
confidence: 90%
“…Additionally, the results indicate that the variables adjust to their long‐run equilibrium at a slow rate, suggesting that short‐run disequilibria persist, which may require policy interventions to promote a more sustainable green economy in the MENA region. Previous research on the relationship between economic growth and energy consumption supports the results of this study, see (Mohammed Idris et al., 2022).…”
Section: Resultssupporting
confidence: 90%
“…Upon examination of the estimated results, it can be observed that there is a negative correlation between renewable energy sources and carbon emissions. Previous studies that have yielded comparable outcomes lend support to this perspective [14,16,21,[23][24][25]27,44]. These findings indicate that the development of sustainable green energy sources (renewable energy sources) should be prioritized over the use of fossil fuels to reduce CO 2 emissions.…”
Section: Discussionsupporting
confidence: 57%
“…Looking at similar studies on the topic, it can be seen that many comprehensive studies have been conducted on the relationship between carbon emissions as the dependent variable and economic development, renewable energy, and non-renewable energy sources. However, most studies examining the relationship between carbon emissions and energy focus on energy consumption [9,14,16,21,27], and very few studies [22] examined the impact of the type of energy generation (renewable and non-renewable) on carbon emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The minute cointegration is confirmed, and the model specifies an error correction form (Aluwani 2023 ). That combines short-run coefficients and long-run adjustments in the single error correction model ( ECM ), which helps to analyse both long-run and short-run parameters simultaneously(Mohammed Idris et al 2023 ). The lag length can be selected by the Akaike information criterion (AIC) and other criteria (Bunnag 2023 ).…”
Section: Methodsmentioning
confidence: 99%